Analisis Hubungan Tradisi Pengasapan Ibu dan Bayi di Indonesia Terhadap Kesehatan: Literature Review - Romadlona, Nohan Arum; Diansasnita, Aisha; Hutami, Citra Kirana; Rosa, Elvania; Husna, Fahrun Nisa' Sifaul; Rahma, Fidela; Fitrah, Iftitah Hanim Tarisa; Novembriani, Rizqie Putri (Universitas Negeri Malang, 2024)
The tradition of smoking mothers and babies remains a cultural practice in Indonesia. The tradition of smoking is a 40-day custom of heating or smoking newborn babies with their mothers using smoke from burning coals. This practice is carried out with the hope that the baby will grow stronger and accelerate the mother's postnatal recovery. The smoking tradition varies greatly depending on the culture in each region, such as the Tatobi, Marapi, Mandadang, Bedaring, and Sei traditions. The objective of this literature study is to analyze the relationship between the implementation of the tradition of smoking mothers and babies in Indonesia and the health of both mother and baby. This study was conducted through a literature review method using eight journal articles obtained from the Google Scholar database published between 2013 and 2022. The study findings indicate that over time, smoking traditions are considered irrelevant to health because smoking on mothers and babies can increase the risk of respiratory disorders and lung function impairment, such as ARI. Minister of Health Regulation number 1077/MENKES/PER/V/2011 states that indoor air pollution that exceeds requirements can be caused by incomplete combustion pollutants produced from biomass fuels.